A Novel Unified Power Quality Conditioning System for Power Quality Improvement and Bidirectional Power Flow Control for Windmill (Global Journals of Research in Engineering, 2013)
This paper proposes a new approach of unified power quality conditioner which is made up of a matrix converter to mitigate the current harmonics, voltage sags and swells and control the power flow with Bi directional capability for windmill. Matrix converter injects the compensation voltage on the load-side, so it is possible to mitigate the voltage sag/swell problems, resulting in an efficient solution for mitigating voltage and current related power quality problems. Thus, the proposed topology can mitigate the voltage fluctuations and current harmonics without energy storage elements and the total harmonic distortion produced by the system also very low. Due to the bidirectional power flow capability of matrix converter the proposed unified power quality conditioner capable to control the power flow of the windmill more over it also transfer power bi -directional. The space-vector modulation (SVM) is used to control the matrix converter. Matlab/Simulink based simulation results are presented to validate the approachstorage elements and the total harmonic distortion produced by the system also very low.Due to the bidirectional power flow capability of matrix converter the proposed unified power quality conditioner capable to control the power flow of the windmill more over it also transfer power bi -directional. The space-vector modulation (SVM) is used to control the matrix converter. Matlab/Simulink based simulation results are presented to validate the approach.
Keywords: matrix converter; unified power quality conditioner; current harmonics; voltage sag/swell; non linear load; windmill; matlab/ simulink